English Teachers' Awareness of Project-Based Learning Strategy and their Attitudes towards its Effectiveness - Sawaftah, Jehan (ِAn-Najah National University, 2020)
This study aimed at investigating the extent of English language teachers' awareness of project-based learning (PBL) strategy, their attitudes towards its effectiveness and the most important obstacles teachers face when applying PBL in their classes. The study examined the effect of the following variables (gender, experience, academic qualification, level of teaching stage and place of graduation) on teachers' attitudes. To achieve the aim of the study, the researcher developed a 39-item questionnaire consisted of three domains: Teachers' awareness of PBL, the effectiveness of using PBL, and the obstacles of applying PBL in the English language classroom. The questionnaire was distributed to (99) male and female English language teachers in the governmental schools in Tubas governorate. Only (76) questionnaires were received and this number was adopted as the final sample size of the study. The results of this descriptive study revealed that teachers are highly aware of the benefits of PBL and have positive attitudes towards its effectiveness in teaching English. However, the results showed that there are a number of challenges that hinder the successful implementation of PBL such as, lack of facilities offered by schools including multimedia centers, laboratory classrooms and flexible learning areas that facilitate group work, lack of time, group work problems, disciplinary problems, crowded classrooms, evaluating students' work, selecting topics suitable for PBL and the difficulty of teaching the curriculum by the use of PBL. Additionally, it was found that there were no statistically significant differences at (α ≤ 0.05) in the English teachers' awareness of PBL strategy and their attitudes towards its effectiveness due to gender in the first and second domains, but there were differences in the third domain and the total score in favor of male teachers. As for the variable of teachers' academic qualification, it has an effect in favor of master degree holders in the first and second domains, but in favor of bachelor degree holders in the third domain. There were also significant differences in the teachers' awareness of PBL and their attitudes towards its effectiveness due to the level of teaching stage in favor of the basic and secondary stage. However, there were no significant differences in the teachers' awareness of PBL and their attitudes towards its effectiveness due to years of experience and place of graduation. In the light of these findings, the researcher recommended the necessity of enriching the Palestinian curriculum with authentic content, training teachers and students on the effective use of PBL and providing the required resources and funding to implement PBL.